Student workshet the development based on stem (sciene, technology, engineering and mathematics) based construct 2 assisted lkpd on excretion system materials to improve student's science literature skills in SMA Negeri 1 Kuala T.P. 2021/2022 - Novita Ruli Fransiska; Hudson Sidabutar (ARKA INSTITUTE, 2022)
Abstract The development of STEM-based LKPD (Science, Technology, Engineering and Mathematics) in this study aims to improve students' scientific literacy skills on excretory system material and is distributed through software construct 2 which has the advantage of not using programming languages . (coding) in its design. The research design applied is a research and development type with a 4-D framework model consisting of four stages, namely: 1) Definition, 2) Design, 3) Development (Develop) and 4) Implementation. The subjects in this study included validators of material experts, learning experts, design experts, educators in the field of biology studies and students of class XI MIPA-4 SMA Negeri 1 Kuala. The data collected and analyzed are quantitative data and qualitative data originating from interview observation sheets, validation sheets from the expert team of validators, educators' assessments and student response questionnaires. The results showed that the LKPD which had been validated by material experts obtained results with an average number of 89.58% with the